1996
DOI: 10.1056/nejm199604113341501
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Multidrug-ResistantMycobacterium tuberculosisduring a Long Airplane Flight

Abstract: The transmission of Mycobacterium tuberculosis that we describe aboard a commercial aircraft involved a highly infectious passenger, a long flight, and close proximity of contacts to the index patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
201
0
22

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(229 citation statements)
references
References 11 publications
6
201
0
22
Order By: Relevance
“…Businesspersons or travelers can become the transmitter of TB if they have been infected by Mycobacterium tuberculosis. The role of public transportation in the transmission of TB has been mentioned in many reports (30,31). However, the potential impact of businesspersons and travelers was not assessed in our study because we could not trace them and obtain reliable information about them.…”
Section: Discussionmentioning
confidence: 93%
“…Businesspersons or travelers can become the transmitter of TB if they have been infected by Mycobacterium tuberculosis. The role of public transportation in the transmission of TB has been mentioned in many reports (30,31). However, the potential impact of businesspersons and travelers was not assessed in our study because we could not trace them and obtain reliable information about them.…”
Section: Discussionmentioning
confidence: 93%
“…For non-uniform contaminant distributions the results of a multizone model has been found to be questionable 21 . Moreover, the air circulation patterns in most commercial aircraft have little airflow in longitudinal direction 22 hence the risk of infectious disease transmission from a contagious passenger to fellow passengers is limited to one or two rows 2,23 . Hence the effect of contaminant released in particular zone of a cabin is expected to remain localized and confined within that zone thus making multizone models inappropriate for such a study.…”
Section: Research Approachmentioning
confidence: 99%
“…1, Lanes 12 and 13) recovered from a Kuwaiti patient and a Filipino patient, respectively, were likely to be epidemiologically related as they yielded identical DNA fragments in touchdown DRE-PCR, contained L463 in the katG gene and their genotypic basis of resistance to isoniazid was due to mutation S315T in the katG gene (Table 1). Though an epidemiological linkage based on direct contact between these patients could not be established, it is possible that the infection was acquired through casual contact or from a common source (13). Molecular epidemiological data reported recently from New York City, a large urban center in the United States (U.S.) with a high proportion of immigrants, have also shown that active disease in majority of patients born outside the U.S. is caused by reactivation of latent M. tuberculosis infection while many TB cases among U.S.-born persons are attributed to recent transmission of infection (10).…”
mentioning
confidence: 99%